EVALUASI KINERJA BAWASLU PADA PEMILIHAN KEPALA DAERAH (PILKADA) DI KABUPATEN MANGGARAI TIMUR TAHUN 2018 - Veronika Ruba Pena; Rina Martini (Jurnal Education and Development, 2023)
Election of regional heads is a general election to elect regional heads and deputy regional heads directly in the Unitary State of the Republic of Indonesia. Election of regional heads directly becomes a new historical journey in the dynamics of the life of the Indonesian nation. Election Oversight Body (Bawaslu) is an election administration body that is tasked with overseeing the holding of elections throughout the territory of the Unitary Republic of Indonesia. This study aims to determine how the implementation of the elections in East Manggarai Regency and to determine the extent of the performance of the Election Oversight Body as a supervisory party in carrying out the oversight function. The method used in this research is qualitative method. The results of this study indicate that the Election Supervisory Body's Performance has been carried out but not yet running optimally. East Manggarai Regency Election Supervisory Body is one part of the organizer of East Manggarai Regency elections in 2018 by developing a supervisory function. East ManggaraiBawaslu needs to make maximum efforts in improving supervision and holding of elections so as to minimize the problems that will arise in the next election. Keywords: Evaluation, Performance, Bawaslu, Regional Head Election